High serum Aspartate transaminase levels on day 3 postliver transplantation correlates with graft and patient survival and would be a valid surrogate for outcome in liver transplantation clinical trials. (29th December 2015) - Robertson, Francis P.; Bessell, Paul R.; Diaz‐Nieto, Rafael; Thomas, Niclas; Rolando, Nancy; Fuller, Barry; Davidson, Brian R.
Summary: Aspartate transaminase, a liver specific enzyme released into serum following acute liver injury, is used in experimental organ preservation studies as a measure of liver IR injury. Whether post‐operative serum transaminases are a good indicator of IR injury and subsequent graft and patient survival in human liver transplantation remains controversial. A single centre prospectively collected liver transplant database was analysed for the period 1988–2012. All patients were followed up for 5 years or until graft failure. Transaminase levels on the 1st, 3rd and 7th post‐operative days were correlated with the patient demographics, operative outcomes, post‐operative complications and both graft and patient survival via a binary logistic regression analysis. Graft and patient survival at 3 months was 80.3% and 87.5%. AST levels on the 3rd ( P = 0.005) and 7th ( P = 0.001) post‐operative days correlated with early graft loss. Patients were grouped by their AST level (day 3): <107iU, 107–1213iU, 1213–2744iU and >2744iU. The incidence of graft loss at 3 months was 10%, 12%. 27% and 59% and 1‐year patient mortality was 12%, 14%, 27% and 62%. Day 3 AST levels correlate with patient and graft outcome postliver transplantation and would be a suitable surrogate endpoint for clinical trials in liver transplantation.